General revoking formulas in canon law and their juridical effects - Huels, John M. 1950- (2012)
vgl. cann. 1502; 1509 CCEO
Keywords: Katholische Kirche -- Sancta Sedes; Katholische Kirche; Katholische Kirche; Katholische Kirche; Katholische Kirche; Gesetz; Aufhebung; Gesetz; Formular; Aufhebung